Novel Sulfonated Ethylene/1-Octene Copolymer Ionomer Nanocomposite: Synthesis and Properties - Pradhan, Sharmila; Scholtissek, Stefanie; Lach, Ralf; Lebek, Werner; Grellmann, Wolfgang; Michler, Goerg H.; Adhikari, Rameshwar (Journal of Nepal Chemical Society, 2013)
The nanocomposites based on sulfonated ethylene/1-octene copolymer (sEOC) and organophilic modified layered silicate were synthesized. The morphology of the ionomeric product was studied with the help of Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM), Fourier Transform Infrared (FTIR) spectroscopy and microhardness measurements. It was shown that via the solution cast technique, the nanocomposite with uniformly distributed filer morphology can be conveniently prepared. The significant enhancement of the mechanical properties due to ionomerization was attested with the help of depth sensing microhardness measurements. It was found that the hardness of ionomer nanocomposite comprising 5 wt.-% layered silicate is approximately four fold of the neat elastomer. DOI: http://dx.doi.org/10.3126/jncs.v28i0.8060 Journal of Nepal Chemical Society Vol.28, 2011 Page : 59-66 Uploaded date: May 7, 2013